SOCIAL RESPONSIBILITY AND SUSTAINABLE DEVELOPMENT PRINCIPLES IN SMALL BUSINESS - Musaev Ozodjon Shavkat ogli (Prospects for innovative technologies in science and education, 2025)
This article explores the integration of social responsibility and sustainable development principles within the small business sector, with a particular focus on the context of Uzbekistan and Central Asia. Small and medium-sized enterprises (SMEs) play a vital role in economic growth, job creation, and local innovation, yet they often face significant challenges in adopting sustainable and socially responsible practices due to limited financial, institutional, and informational resources. Drawing on international frameworks such as the United Nations Sustainable Development Goals (SDGs) and national initiatives like Uzbekistan’s Strategy for the Transition to a Green Economy (2019–2030), the paper examines how CSR can serve as both a moral commitment and a strategic advantage for SMEs. It discusses barriers including financial constraints, weak policy support, and cultural perceptions, while offering practical recommendations such as tax incentives, green financing, education-based awareness, and digital innovation. The article also highlights local case studies demonstrating how eco-friendly, community-based, and women-led enterprises contribute to inclusive and sustainable development. Ultimately, it argues that empowering small businesses to act responsibly is essential for achieving long-term social equity, environmental balance, and economic resilience across the region.